2015
DOI: 10.3109/13561820.2015.1063482
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the Electronic Health Record into high-fidelity interprofessional intensive care unit simulations

Abstract: With the rapid adoption of electronic health records (EHR), there is a growing appreciation for the central role they play in clinical decision making and team communication, with many studies documenting new safety issues with integration of the EHR into the clinical enterprise. To study these issues, we created a high-fidelity simulation instance of our clinical EHR. In this paper, we describe the impact of integrating the EHR into high-fidelity, interprofessional intensive care unit (ICU) simulations, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…difficulty logging into system (Ilie, Van Slyke, Parikh, & Courtney, 2009). Informaticists should also be included in the healthcare team and new technologies should be tested through realistic, simulated environments to be improved prior to implementation in the real-world setting (Elias, Barginere, Berry, & Selleck, 2015; Gold, Tutsch, Gorsuch, & Mohan, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…difficulty logging into system (Ilie, Van Slyke, Parikh, & Courtney, 2009). Informaticists should also be included in the healthcare team and new technologies should be tested through realistic, simulated environments to be improved prior to implementation in the real-world setting (Elias, Barginere, Berry, & Selleck, 2015; Gold, Tutsch, Gorsuch, & Mohan, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…To amplify this paradigm, a number of studies conducted by our group and others have suggested that providers across multiple professions have difficulty in using the EHR as manifested by issues with data finding, recognition of patient safety issues, and impairment in clinical decision making [ 4 , 5 ]. Additionally, recent studies revealed that problems associated with clinicians’ selective data gathering or selective data interpretation can lead to increased patient harm, a phenomenon that has also been identified and replicated in simulation exercises [ 6 , 7 ]. These issues are not just isolated to physicians: recent work from our group has suggested that the phenomenon affects nurses and pharmacists at all levels of training, implying a global problem related to human EHR interfaces [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the majority (14/24) of the studies was either to improve learning skills of medical trainees and clinicians or to teach technical and non-technical skills. 4,[41][42][43][44][45][46][46][47][48][49][50][51][52] Of these studies seven had the objective of showing that simulation-based EHR training can enhance the teaching of students. [53][54][55][56][57][58][59] One study investigated the practicality of integrating an eye tracker into an EHR simulation environment, 60 one study sought to understand EHR-related communication and data management skills, 53 and one study used high-fidelity EHR-based simulation to understand learners struggling with clinical efficiency and decision making.…”
Section: Study Characteristicsmentioning
confidence: 99%